2013
DOI: 10.2110/jsr.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Syndepositional Deformation Features In High-Relief Carbonate Platforms: Long-Lived Conduits for Diagenetic Fluids

Abstract: Syndepositional faults and fractures are known to affect early fluid flow in carbonate platforms. Less clear is whether they are active fluid conduits throughout the entire history of the platform strata. Syndeformational fractures in Permian (late Guadalupian) carbonates exposed in Dark Canyon, Guadalupe Mountains, New Mexico, U.S.A., address this question. Transmitted-light and cathodoluminescent petrography, stable-isotope and fluid-inclusion analyses, and clumpedisotope thermometry show that there were mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 61 publications
(140 reference statements)
12
49
0
1
Order By: Relevance
“…Our analyses extend the data set to include fore-reef slope facies and therefore provide a more complete picture of potential spar precipitation events. While the fluids responsible for precipitating these spars may well have been sourced along faults as indicated by the Budd et al (2013) study, they also penetrated unfaulted formation in the fore-reef slope. The clumped isotope data from this study and Budd et al (2013) are evaluated together, along with previously reported outcrop and core relationship data (Scholle et al, 1992).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Our analyses extend the data set to include fore-reef slope facies and therefore provide a more complete picture of potential spar precipitation events. While the fluids responsible for precipitating these spars may well have been sourced along faults as indicated by the Budd et al (2013) study, they also penetrated unfaulted formation in the fore-reef slope. The clumped isotope data from this study and Budd et al (2013) are evaluated together, along with previously reported outcrop and core relationship data (Scholle et al, 1992).…”
Section: Introductionmentioning
confidence: 89%
“…While the fluids responsible for precipitating these spars may well have been sourced along faults as indicated by the Budd et al (2013) study, they also penetrated unfaulted formation in the fore-reef slope. The clumped isotope data from this study and Budd et al (2013) are evaluated together, along with previously reported outcrop and core relationship data (Scholle et al, 1992). These results indicate that late stage spar precipitation was extensive, occurred long after deposition and included a significant meteoric fluid component, with cementation likely occurring during uplift and not during burial.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations